MALAYSIAN POP MUSIC IN THE MINORITY LANGUAGE: A TOOL FOR FORGING UNITY AND A COMMON IDENTITY? - Collin, Jerome; Esther, John Perry; Ting, Su Hie (ACADEMIA INDUSTRY NETWORKS, 2022)
Numerous studies have demonstrated thatmodern popular songs in the majority language can forgea sense of national identity, unity, and pride among the masses. However, popular songs written and sung in the minority language have the same ability and even more. The present study examined this disparityby gathering the views and opinions of the Malaysian masses through self-administered surveys regarding Lagu pop Iban (Iban pop song) and its connectionto identity and unity. The findings showedthat the respondents, most of whom originated fromthe Malaysian state of Sarawak, possesseda good knowledge of Iban pop songs, displayed positiveattitudes towards them and engaged with this music genre in variedways. The findings also showedthere was an agreementamong the respondents regarding Iban pop songs' ability to foster a commonsense of belonging and a shared identity over time, despite their differentviews on this matter. One of the implications of these findings is that the role of music in minority languages should be accepted and recognized as a tool for forging unity and a common identitywithin the context of multiracial, multilingual, and multicultural nation-states.